A substitution mutation in a conserved domain of mammalian acetate-dependent acetyl CoA synthetase 2 results in destabilized protein and impaired HIF-2 signaling. - Jason S Nagati; Min Xu; Trent Garcia; Sarah A Comerford; Robert E Hammer; Joseph A Garcia (PLoS ONE, 2019)
The response to environmental stresses by eukaryotic organisms includes activation of protective biological mechanisms, orchestrated in part by transcriptional regulators. The tri-member Hypoxia Inducible Factor (HIF) family of DNA-binding transcription factors include HIF-2, which is activated under conditions of oxygen or glucose deprivation. Although oxygen-dependent protein degradation is a key mechanism by which HIF-1 and HIF-2 activity is regulated, HIF-2 is also influenced substantially by the coupled action of acetylation and deacetylation. The acetylation/deacetylation process that HIF-2 undergoes employs a specific acetyltransferase and deacetylase. Likewise, the supply of the acetyl donor, acetyl CoA, used for HIF-2 acetylation originates from a specific acetyl CoA generator, acetate-dependent acetyl CoA synthetase 2 (Acss2). Although Acss2 is predominantly cytosolic, a subset of the Acss2 cellular pool is enriched in the nucleus following oxygen or glucose deprivation. Prevention of nuclear localization by a directed mutation in a putative nuclear localization signal in Acss2 abrogates HIF-2 acetylation and blunts HIF-2 dependent signaling as well as flank tumor growth for knockdown/rescue cancer cells expressing ectopic Acss2. In this study, we report generation of a novel mouse strain using CRISPR/Cas9 mutagenesis that express this mutant Acss2 allele in the mouse germline. The homozygous mutant mice have impaired induction of the canonical HIF-2 target gene erythropoietin and blunted recovery from acute anemia. Surprisingly, Acss2 protein levels are dramatically reduced in these mutant mice. Functional studies investigating the basis for this phenotype reveal multiple protein instability domains in the Acss2 carboxy terminus. The findings described herein may be of relevance in the regulation of native Acss2 protein as well as for humans carrying missense mutations in these domains.